Deep and shallow in Arabic orthography: New evidence from reading performance of elementary school native Arab readers. Issue 2 (2nd July 2016) - Taha, Haitham
ABSTRACT: The current study tested the impact of vowelisation on reading speed and accuracy of Arabic words among skilled and poor native Arabic readers using a cross-sectional procedure. One hundred and forty-three skilled and 146 poor native Arab readers from northern Israel (second, fourth and sixth grades) read two lists of full vowelised and non-vowelised words. The results indicate that among the readers, the non-vowelised words were read more accurately than the vowelised words. For the skilled poor readers, such significant differences were found within the older reader groups only (the fourth and sixth grades). Differences in the speed of reading vowelised and non-vowelised words were found within the older groups only in both groups of readers. The results are discussed in light of different approaches in the field of visual word recognition. It is suggested that vowelisation for skilled and older readers could cause a visual load during the process of the visual recognition of words and may be considered as 'redundant information'.